Risk assessment of second primary cancer according to histological subtype of non-Hodgkin lymphoma. Issue 10 (3rd October 2015) - Rossi, Cédric; Jégu, Jérémie; Mounier, Morgane; Dandoit, Mylène; Colonna, Marc; Daubisse-Marliac, Laetitia; Trétarre, Brigitte; Ganry, Olivier; Guizard, Anne-Valérie; Bara, Simona; Bouvier, Véronique; Woronoff, Anne-Sophie; et al.
Abstract : Non-Hodgkin lymphoma (NHL) represents a heterogeneous group of diseases that are known to carry a considerable risk of second primary cancer (SPC). However, little attention has been paid to SPC risk assessment according to NHL subtypes. Data from 10 French population-based cancer registries were used to establish a cohort of 7546 patients with a first diagnosis of NHL (eight subtypes) between 1989 and 2004. Standardized incidence ratios (SIRs) of metachronous SPC were estimated. Among the 7546 patients diagnosed with a NHL, the overall SPC risk was 25% higher than that in the reference population (SIR = 1.25, 95% confidence interval 1.15–1.36). In univariate analysis, the SPC risk differed by lymphoma subtype. Interestingly, multivariate analysis showed that SPC risk did not differ significantly across NHL subtypes after adjustment for the other covariates ( p = 0.786). Patients with NHL have an increased risk of SPC that is not influenced by the histological NHL subtype.